Corporate Politics Perception and Career Satisfaction: Mediating Role of Ingratiation Behavior - Bhattarai, Ganesh (Nepal Journal of Multidisciplinary Research, 2023)
This research sought to evaluate the influence of employees' perceived corporate politics on their career satisfaction within their current work settings. Additionally, the study investigated how employees' efforts to ingratiate themselves mediate the relationship between perceived corporate politics and career satisfaction. The study collected cross-sectional perceptual data from employees in the banking industry in Nepal, analyzing 725 responses using a positivist research approach. Data analysis employed a hierarchical regression model with SPSS, yielding several significant findings. Firstly, it was observed that employees' perceptions of corporate politics harmed their career satisfaction. Secondly, the study found that employees' ingratiation behavior mediated the association between perceived corporate politics and career satisfaction. Thirdly, the overall impact of perceived corporate politics on career satisfaction was -0.17 (indicated as B = -0.17). Fourthly, the direct influence of perceived corporate politics on career satisfaction was -0.35 (represented by B = -0.35). Lastly, the indirect impact of perceived corporate politics on career satisfaction through ingratiation was 0.18 (B = 0.18). Based on these findings, the study suggests implications and directions for future research in this domain.